1998
DOI: 10.1038/sj.ejcn.1600517
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia in pregnancy—a cross-sectional study in Singapore

Abstract: Objective: To determine the prevalence and predictors of anaemia in pregnancy in Singapore. Design: Hospital based case controlled study. Setting: National University Hospital, between January±December 1993. Subjects: All women delivered at the National University Hospital, Singapore in 1993 had their haemoglobin estimated. If it was less than 11 gmadl, blood was taken to establish the cause of anaemia. Data was also collected with regard to their antenatal progress, and factors predisposing to anaemia in preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
46
4
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 16 publications
6
46
4
1
Order By: Relevance
“…This result is almost consistent with across sectional study carried out in Gonder (23%) and in the University of Port Harcourt Teaching Hospital, Port Harcourt in Nigeria which had shown a prevalence rate of 23.2% [12,13]. In contrast to this study, a study conducted at Health Promotion Hospital Nakhonsawan, in Thailand showed a prevalence rate of 14.1% [14].This may be due to a difference in socio-economic and educa tional status between the study populations in the two study areas.…”
Section: Discussionsupporting
confidence: 90%
“…This result is almost consistent with across sectional study carried out in Gonder (23%) and in the University of Port Harcourt Teaching Hospital, Port Harcourt in Nigeria which had shown a prevalence rate of 23.2% [12,13]. In contrast to this study, a study conducted at Health Promotion Hospital Nakhonsawan, in Thailand showed a prevalence rate of 14.1% [14].This may be due to a difference in socio-economic and educa tional status between the study populations in the two study areas.…”
Section: Discussionsupporting
confidence: 90%
“…For nonpregnant and non-lactating women, a haemoglobin cut-off of 12 gadl is used to de®ne anaemia (Cook & Skikne, 1989;Institute of Medicine (US), 1993). Previous studies have used Hb cut-off values of either 10 gadl (Lao et al, 1996), 11 gadl (Singh et al, 1998) or 12 gadl (Kuvibidila et al, 1994). Although it has been suggested that the haemodilution effect of pregnancy is still apparent at 6 ± 8 weeks postpartum (Taylor & Lind, 1979), our ®ndings showed that the mean Hb level of subjects had increased to !…”
Section: Discussioncontrasting
confidence: 55%
“…The prevalence of anemia in our study was similar to previous reports conducted in Korea (Lim and Kim, 1998;Yu et al, 1999) and in Asia (Hui et al, 1995). Anemia or iron deficiency during pregnancy is associated with intrauterine growth retardation, premature birth, low birth weight, increased labor time, higher risk of infection, elevated maternal and prenatal mortality, muscle dysfunction and low physical capacity (Murphy et al, 1986;Lu et al, 1991;Scholl and Hediger, 1994;Singh et al, 1998;Zhou et al, 1998;Yip, 2000). Lone et al (2004) reported the association between low maternal Hb level and Apgar score o5 at 1 min, which is an index of health status of newborn babies.…”
Section: Discussionmentioning
confidence: 99%
“…In Asia, the prevalence of anemia was estimated to be 44% in non-pregnant and 60% in pregnant women (Rush, 2000). At least 50% of the anemia has been attributed to iron deficiency (DeMaeyer and Adiels-Tegman, 1985;Singh et al, 1998). Maternal iron deficiency anemia increases the risk of premature delivery and subsequent low birth weight, and may contribute to low iron status and poor health of infants (Allen, 2000;Scholl and Reilly, 2000;Kaiser and Allen, 2002).…”
Section: Introductionmentioning
confidence: 99%